ARTIKULASI PENGGUNAAN MEDIA KLIPING DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN PADA PESERTA DIDIK KELAS III SEKOLAH DASAR NEGERI 18 SUNGAI KAKAP - Khairunnisa, Khairunnisa; Zainuddin, Zainuddin; Nurhadi, Nurhadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study are to: Â (1) describe that the learning media of clipping is able to raises the values of togetherness which can be perceived by the students; (2) describe that the learning media of clipping is able to improve the sense of togetherness between the students within their society; (3) describe several factors that is related to the learning media of clipping in Civic Education. The method used for this research was descriptive method in form of a Survey Studies. The study was conducted to the third grade students of SDN 18 Sungai Kakap. The data for this researh was collected through direct observation, direct communication, indirect communication, and documentary technique. The data collection tools used were interview questionnaire guide, checklist, survey notes, and written notes. The collected data were analysed by using chi-square formula. The results of the study shows that rate of 24.08 are obtained from the studentâ€™s answer sheet, meaning that the purpose of learning media of clipping are containing the values of togetherness which can be perceived by the students in learning of civic education. Learning media of clipping is able to improve the sense of togetherness between the students within their society, with the result of 21.12. The factors that are related to the purpose of the medium results the rate of 24.44. The purpose of the learning media of clipping has corresponded to the related lessons, with the result of 17.68.Keywords: Learning Media, The Medium of Clipping, Civic Education